Fatty Acids 2017
DOI: 10.5772/67693
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Factors that Determine the Meat Fatty Acids Composition

Abstract: In relation the nutritional atributes of beef meat quality, the composition of faty acid is important not only because it afects the meat palatability, but also it can afect the human health. The faty acids harmful to human health have received atenuating atention in recent years. Some studies, with taurine breed, have shown that there is a genetic variation for the trait faty acid proile of the meat and, therefore, the possibility of genetic improvement of this trait in beef catle. Meantime, in zebu catle, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
(84 reference statements)
1
3
0
Order By: Relevance
“…Myristic acid, palmitic acid, stearic acid and pentadecanoic acid were the major SFA in the beef of cattle under the study. Similarly, a study reported the dominant SFAs in cattle fat as myristic (C14:0), palmitic (C16:0), and stearic (C18:0) acids [39]. The age and breeds of cattle had a significant influence (P < 0.05) on fatty acid profiles in the present study.…”
Section: Types Of Saturated and Unsaturated Fatty Acid In Beef Fromsupporting
confidence: 78%
“…Myristic acid, palmitic acid, stearic acid and pentadecanoic acid were the major SFA in the beef of cattle under the study. Similarly, a study reported the dominant SFAs in cattle fat as myristic (C14:0), palmitic (C16:0), and stearic (C18:0) acids [39]. The age and breeds of cattle had a significant influence (P < 0.05) on fatty acid profiles in the present study.…”
Section: Types Of Saturated and Unsaturated Fatty Acid In Beef Fromsupporting
confidence: 78%
“…The breast muscle of chicken is highly favored due to its rich content of fatty acids, which directly influence the taste, flavor, tenderness, and nutritional value of chicken meat [1]. However, the composition and content of these fatty acids are regulated by various factors such as genetics and nutrition [2][3][4][5]. Therefore, it is of great significance to understand the molecular regulatory mechanisms behind the fatty acid composition and content in chicken breast muscle.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the amount of fatty acids in beef is crucial for the reason that it affects the lusciousness of the beef and human well‐being. But the effects of harmful fatty acids on human health have received less attention in some regions of the world (de Lemos et al., 2017). In this regard, several studies have been done in various parts of the world to determine the role of transcription factors in beef cattle adipogenesis and lipogenesis.…”
Section: Introductionmentioning
confidence: 99%